2021
DOI: 10.3390/nu13082597
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Transitions in Food Insecurity Status during the Early Stages of the COVID-19 Pandemic among Ethnically Diverse Households in Central Texas

Abstract: Food insecurity increased substantially in the USA during the early stages of the 2020 COVID-19 pandemic. The purpose of this study was to identify potential sociodemographic and food access-related factors that were associated with continuing or transitioning into food insecurity in a diverse population. An electronic survey was completed by 367 households living in low-income communities in Central Texas during June–July 2020. Multinomial logistic regression models were developed to examine the associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Additionally, middle-and lowincome participants noted that they had to cook all the time (to feed their children) and were worried about the extent of consumption of food and drinks and the cost involved (n = 18). This finding supports the results of other studies that found that working mothers experienced more anxiety concerning their ability to afford food for the household than women without children in their homes [26,45].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, middle-and lowincome participants noted that they had to cook all the time (to feed their children) and were worried about the extent of consumption of food and drinks and the cost involved (n = 18). This finding supports the results of other studies that found that working mothers experienced more anxiety concerning their ability to afford food for the household than women without children in their homes [26,45].…”
Section: Discussionsupporting
confidence: 92%
“…27 The higher financial hardship seen among this population was associated with a greater risk of food insufficiency. Consistent with other research, 2,4,5,11,13,19,27-29 our study showed that food insecurity during the pandemic disproportionately affected Black and Hispanic individuals/households, with approximately half of all Black and Hispanic participants reporting food insecurity (compared to 31% overall). Our data also indicated that Black and Hispanic respondents within the most affected industries tended to have lower incomes (as reported in Visit 1) than White respondents, which combined with lost income during the pandemic may have exacerbated the disparity.…”
Section: Discussionsupporting
confidence: 91%
“…This widening disparity has been observed in other studies. 1,[9][10][11][12][13] The federal government passed legislation including the Families First Coronavirus Response Act (FFCRA) and the Coronavirus Aid, Relief and Economic Security Act (CARES) in March 2020 to help provide economic relief by increasing unemployment benefits, providing direct payments ("stimulus checks") to eligible individuals, and increasing support for child nutrition programs and the Supplemental Nutrition Assistance Program (SNAP). 14,15 Given the widening racial/ethnic disparities, not everyone may have benefited equally from this additional legislation.…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity rates in the United States (U.S.) rapidly increased during the COVID-19 pandemic [1,2], with elevated rates in Black, Latino, and low-income households [3][4][5]. Food insecurity is associated with greater health care expenditures [6] and worse health behaviors and outcomes [7], including lower-quality diet [8][9][10], diet-related chronic illness (e.g., diabetes, cardiovascular disease) [7,[11][12][13][14][15], and premature death [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic's employment crisis exacerbated economic instability and food insecurity among marginalized populations. Economic impacts disproportionately affected U.S. Latino households [1,4], who faced a multitude of structural barriers that influenced their food security status and diet [18]. Latinos struggled with increased economic and health vulnerabilities during the pandemic since they were concentrated in lower-wage occupations [19], more likely to work outside the home, and less likely to obtain economic aid through stimulus checks or unemployment benefits [20,21], thereby increasing their risk of food insecurity.…”
Section: Introductionmentioning
confidence: 99%